COST EFFECTIVENESS ANALYSIS PENGGUNAAN ANTIBIOTIK INJEKSI PADA PASIEN BRONKOPNEUMONIA DI KLINIK PRATAMA RAWAT INAP GRAHA MEDIKA PATI - Yulia Pratiwi; Ahmad Izul Khilmi; Wildayanti Wildayanti; Mera Putri Pratitis; Aprillia Puspitasari Tunggadewi (2026)
Bronchopneumonia is an infectious lung disease affecting one or more lobes of the lung, characterized by patches of infiltrate caused by bacteria, viruses, fungi, and foreign objects. The primary treatment for bronchopneumonia is antibiotic therapy. Inappropriate antibiotic use can have adverse effects, including the emergence of bacterial resistance to antibiotics, resulting in longer patient care times and higher treatment costs. Therefore, a cost-effectiveness analysis of antibiotic injection treatment for bronchopneumonia patients is necessary. The purpose of this study was to determine the cost-effectiveness of the use of antibiotic injections in bronchopneumonia patients at the Graha Medika Pati Inpatient Clinic. This study was non-experimental or observational. The sampling technique used was a total sampling that met the inclusion and exclusion criteria. Data collection was conducted retrospectively. Data taken from medical records and patient financial information includes patient characteristics data (medical record number, age, patient name, gender, length of treatment, comorbidities), patient clinical data (diagnosis, radiology, and laboratory results), drug use data (antibiotic drug class), and total treatment cost data (laboratory, radiology, antibiotic drug costs, and treatment costs). The prevalence of bronchopneumonia patients at the Graha Media Pati Inpatient Primary Clinic in 2023 was male (52%) and female (48%). The prevalence of the most elderly and very elderly years is every 20 patients (32%), the most common comorbidities are typhoid fever, as many as 29 (47%). The ACER value of Ceftriaxone Inj. is higher, which is Rp. 30,938, compared to the ACER value of Levofloxacin Inj. of Rp. 26,012, ICER value Rp. 459,652.